CNT-based antistatic MPPE composite material and preparation method thereof

Through specific material reaction and treatment techniques, anti-static MPPE composite materials based on CNT were prepared, solving the problems of unstable anti-static effect and poor toughness of existing MPPE composite materials, and achieving better anti-static and mechanical properties.

CN119708813AActive Publication Date: 2025-03-28JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD

Patent Information

Application Number
CN202510233178.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

At this stage, the anti-static effect of MPPE composite materials is unstable and has poor toughness, which affects its normal use.

Method used

By performing specific reactions and treatments on materials such as functionalized polyphenylene ether, hydroxylated polystyrene and carbon nanotubes, modified polyphenylene ether, modified polystyrene and modified carbon nanotubes, and CNT-based anti-static MPPE composite materials are synthesized through extrusion granulation technology.

Benefits of technology

The antistatic and mechanical properties of composite materials are significantly improved, their resistance to shocks is enhanced, and the toughness and antistatic stability of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a CNT-based antistatic MPPE composite material and a preparation method thereof, the composite material comprises the following raw materials by weight: 40-50 parts of modified polyphenyl ether, 40-50 parts of modified polystyrene, 10-15 parts of modified carbon nanotubes and 1-1.5 parts of zinc oxide, the modified carbon nanotubes are added into the composite filler, and the modified carbon nanotubes have a good conductive effect, so that the antistatic performance of the composite material is improved. And when the modified polyphenyl ether, the modified polystyrene, the modified carbon nanotubes and the zinc oxide are subjected to melt blending, under the action of the zinc oxide, the modified polyphenyl ether and the modified polystyrene are compounded and can be subjected to a DA reaction with maleimide on the modified carbon nanotubes to form dynamic crosslinking, so that the antistatic effect of the composite material is improved. Dynamic crosslinking can absorb and disperse energy when the composite material is impacted, and enables a molecular chain segment to generate greater motion when the composite material is impacted, so that deformation of the material is facilitated without breakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of MPPE composite materials, and in particular to an antistatic MPPE composite material based on CNT and a preparation method thereof. Background Art

[0002] Modified polyphenylene ether (MPPE) is mainly obtained by blending polyphenylene ether and polystyrene. The presence of benzene ring in polyphenylene ether increases the barrier for rotation within the molecular chain segment. The molecular chain is a rigid chain, without hydrolyzable groups and polar groups, and the structure is relatively regular and symmetrical, which makes polyphenylene ether have excellent heat resistance, hydrolysis stability, low moisture absorption rate, excellent dielectric properties and high glass transition temperature. It is widely used in various industries, but polyphenylene ether itself also has disadvantages, such as poor electrical conductivity, easy to generate static electricity during long-term use, and poor impact toughness. It is easy to have brittle fracture, which affects the use of modified polyphenylene ether. Carbon nanotubes (CNT) are a common additive to increase the antistatic properties of modified polyphenylene ether, but the effect of simple melt blending is not good, resulting in poor antistatic effect of the prepared modified polyphenylene ether, which in turn affects normal use. Summary of the invention

[0003] The purpose of the present invention is to provide an antistatic MPPE composite material based on CNT and a preparation method thereof, which solves the problem that the antistatic effect of the MPPE composite material at the current stage is unstable and the toughness is poor.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing an antistatic MPPE composite material based on CNT specifically comprises the following steps: Step A1: functionalized polyphenylene ether, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether are mixed, and reacted for 1-1.5 hours at a speed of 200-300 r / min and a temperature of 0°C to obtain modified polyphenylene ether; styrene, 4,4'-azobis(4-cyanopentanol) and toluene are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 10-12 hours at a speed of 120-150 r / min and a temperature of 70-75°C to obtain hydroxylated polystyrene; Step A2: hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF are mixed, and reacted for 2-3 hours at a speed of 200-300 r / min and a temperature of 0°C to obtain modified polystyrene; carbon nanotubes are dispersed in ethanol, and stirred at a speed of 200-300 r / min and a temperature of 60-70°C, and KH550 and deionized water are added, and reacted for 2-3 hours to obtain amino carbon nanotubes; Step A3: Evenly mix the amino carbon nanotubes, maleic anhydride, triethylamine and toluene, and reflux for reaction at a speed of 60-80 r / min and a temperature of 115-120° C. for 2-3 hours to obtain modified carbon nanotubes. Weigh the following raw materials in parts by weight: 40-50 parts of modified polyphenylene ether, 40-50 parts of modified polystyrene, 10-15 parts of modified carbon nanotubes and 1-1.5 parts of zinc oxide. Extrude and granulate the raw materials at a temperature of 230-240° C. to obtain an antistatic MPPE composite material based on CNT.

[0005] Furthermore, the amount ratio of the functionalized polyphenylene ether, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether described in step A1 is 1 g:2 g:0.7 g:1 mL:50 mL, and the mass ratio of styrene, 4,4'-azobis(4-cyanopentanol) and toluene is 20:1.2:20.

[0006] Furthermore, the amount ratio of the hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step A2 is 1 g:1.8 g:0.7 g:1 mL:50 mL, and the amount of KH550 is 2% of the mass of the carbon nanotubes.

[0007] Furthermore, the amount ratio of the amino carbon nanotubes, maleic anhydride, triethylamine and toluene in step A3 is 1 g:50 mmol:150 mmol:30 mL.

[0008] Further, the functionalized polyphenylene ether is prepared by the following steps: Step B1: Sodium hydroxide, isopropanol and methanol are mixed evenly, and stirred for 3-5 hours at a speed of 120-150 r / min and a temperature of 50-60° C., and then 1,3-divinyltetramethyldisiloxane and toluene are added, and the reaction is continued for 30-40 minutes to obtain an intermediate, and the intermediate, pentaerythritol tetrathioglycolate, benzophenone and DMF are mixed evenly, and the reaction is carried out for 1-1.5 hours at a speed of 60-80 r / min and irradiation with 365 nm ultraviolet light to obtain a starting monomer; Step B2: octamethylcyclotetrasiloxane and concentrated sulfuric acid are uniformly mixed, and reacted for 3-5 hours at a speed of 120-150 r / min and a temperature of 75-80° C. to obtain a chain extension monomer, and the starting monomer, the chain extension monomer and DMF are mixed, and reacted for 10-15 hours at a speed of 150-200 r / min and a temperature of 60-65° C., and then cooled to 10-15° C., dimethylchlorosilane is added, and the reaction is continued for 10-15 hours to obtain a modified monomer; Step B3: Evenly mix the modified monomer, 4-vinylphenol, chloroplatinic acid and DMF, and react at a speed of 200-300 r / min and a temperature of 70-80°C for 2-3 hours to obtain a functional monomer; evenly mix the functional monomer, 2,6-dimethylphenol, cupric chloride, pyridine and DMF, and react at a speed of 120-150 r / min, a temperature of 25-30°C and an oxygen atmosphere for 2-3 hours to obtain a functionalized polyphenylene ether.

[0009] Furthermore, the amount ratio of sodium hydroxide, isopropanol, methanol and 1,3-divinyltetramethyldisiloxane in step B1 is 200mmol:35mL:35mL:100mmol, the molar ratio of the intermediate to pentaerythritol tetrathioglycolate is 4:1, and the amount of benzophenone is 1% of the mass of the intermediate.

[0010] Furthermore, the amount of concentrated sulfuric acid used in step B2 is 1.5% of the mass of octamethylcyclotetrasiloxane, and the molar ratio of the starting monomer, the chain extension monomer and dimethylchlorosilane is 1:4:4.2.

[0011] Furthermore, the molar ratio of the modified monomer described in step B3 to 4-vinylphenol is 1:4, and the amount ratio of the functional monomer, 2,6-dimethylphenol, copper chloride, pyridine and DMF is 1g:20g:0.6g:50mL:200mL.

[0012] A CNT-based antistatic MPPE composite material is prepared by the above preparation method.

[0013] The invention provides a CNT-based antistatic MPPE composite material comprising the following raw materials: modified polyphenylene ether, modified polystyrene, modified carbon nanotubes and zinc oxide. The modified polyphenylene ether is prepared by using functionalized polyphenylene ether and furanoyl chloride as raw materials, 4-dimethylaminopyridine as a catalyst and triethylamine as an acid-binding agent to react so that the phenolic hydroxyl group on the modified polyphenylene ether reacts with the acyl chloride on the furanoyl chloride to obtain the modified polyphenylene ether. The modified polystyrene is prepared by free radical polymerization of styrene and 4,4'-azobis(4-cyanopentanol) to obtain hydroxylated polystyrene. The hydroxylated polystyrene is reacted with furanoyl chloride so that the hydroxyl group on the hydroxylated polystyrene reacts with the acyl chloride on the furanoyl chloride to obtain the modified polystyrene. The carbon nanotubes are treated with KH550 so that amino groups are grafted on the surface to obtain aminoated carbon nanotubes. The aminoated carbon nanotubes are reacted with maleic anhydride to form maleimide on the surface of the carbon nanotubes to obtain the modified carbon nanotubes.

[0014] The functionalized polyphenylene ether is prepared by reacting 1,3-divinyltetramethyldisiloxane with sodium hydroxide to form a sodium silanol structure, and preparing an intermediate. The intermediate is reacted with pentaerythritol tetrathioglycolate under light, so that the double bond on the intermediate reacts with the thiol group on the pentaerythritol tetrathioglycolate to prepare a starting monomer. Octamethylcyclotetrasiloxane is ring-opening polymerized with concentrated sulfuric acid as a catalyst to prepare a chain extension monomer. The starting monomer and the chain extension monomer are reacted and then end-capped with dimethylchlorosilane to prepare a modified monomer. The modified monomer is reacted with 4-vinylphenol, so that the Si-H bond on the modified monomer reacts with the double bond on the 4-vinylphenol to prepare a functional monomer. The functional monomer is subjected to an oxidative coupling reaction with 2,6-dimethylphenol to prepare the functionalized polyphenylene ether.

[0015] Modified carbon nanotubes are added to the composite filler. The modified carbon nanotubes have a good conductive effect, so that the composite material forms a conductive path and increases its antistatic effect. When the modified polyphenylene ether, modified polystyrene, modified carbon nanotubes and zinc oxide are melt-blended, under the action of zinc oxide, the composite of the modified polyphenylene ether and the modified polystyrene can undergo a DA reaction with the maleimide on the modified carbon nanotubes to form dynamic crosslinks in the composite material. The dynamic crosslinks can absorb and disperse energy when the composite material is impacted, and enable the molecular chain segments to move more when impacted, thereby helping the material to deform without breaking, thereby greatly improving the impact resistance of the material. The star-shaped structure of the modified polyphenylene ether and the chain-shaped structure of the modified polystyrene are combined to form a semi-interpenetrating grid structure, thereby greatly improving the mechanical properties of the composite material. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Example 1: A method for preparing an antistatic MPPE composite material based on CNT, comprising the following steps: Step A1: functionalized polyphenylene ether, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether are mixed, and reacted at a speed of 200 r / min and a temperature of 0°C for 1 h to obtain modified polyphenylene ether; styrene, 4,4'-azobis(4-cyanopentanol) and toluene are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 120 r / min and a temperature of 70°C for 10 h to obtain hydroxylated polystyrene; Step A2: hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF were mixed, and reacted for 2 hours at a speed of 200 r / min and a temperature of 0°C to obtain modified polystyrene; carbon nanotubes were dispersed in ethanol, and KH550 and deionized water were added under stirring at a speed of 200 r / min and a temperature of 60°C, and reacted for 2 hours to obtain amino carbon nanotubes; Step A3: Evenly mix the amino carbon nanotubes, maleic anhydride, triethylamine and toluene, and reflux for reaction at a speed of 60 r / min and a temperature of 115°C for 2 hours to obtain modified carbon nanotubes. Weigh the following raw materials in parts by weight: 40 parts of modified polyphenylene ether, 40 parts of modified polystyrene, 10 parts of modified carbon nanotubes and 1 part of zinc oxide. Extrude and granulate the raw materials at a temperature of 230°C to obtain an antistatic MPPE composite material based on CNT.

[0018] The amount ratio of the functionalized polyphenylene ether, furanyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether described in step A1 is 1 g:2 g:0.7 g:1 mL:50 mL, and the mass ratio of styrene, 4,4'-azobis(4-cyanopentanol) and toluene is 20:1.2:20.

[0019] The amount ratio of hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step A2 is 1 g:1.8 g:0.7 g:1 mL:50 mL, and the amount of KH550 is 2% of the mass of the carbon nanotubes.

[0020] The amount ratio of the amino carbon nanotubes, maleic anhydride, triethylamine and toluene described in step A3 is 1 g:50 mmol:150 mmol:30 mL.

[0021] The functionalized polyphenylene ether is prepared by the following steps: Step B1: Sodium hydroxide, isopropanol and methanol are mixed evenly, and stirred for 3 hours at a speed of 120 r / min and a temperature of 50° C., and then 1,3-divinyltetramethyldisiloxane and toluene are added, and the reaction is continued for 30 minutes to obtain an intermediate, and the intermediate, pentaerythritol tetrathioglycolate, benzophenone and DMF are mixed evenly, and the reaction is carried out for 1 hour at a speed of 60 r / min and irradiation with 365 nm ultraviolet light to obtain a starting monomer; Step B2: octamethylcyclotetrasiloxane and concentrated sulfuric acid are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 75° C. for 3 hours to obtain a chain extension monomer, and the starting monomer, the chain extension monomer and DMF are mixed, and reacted at a speed of 150 r / min and a temperature of 60° C. for 10 hours, and then cooled to 10° C., dimethylchlorosilane is added, and the reaction is continued for 10 hours to obtain a modified monomer; Step B3: Evenly mix the modified monomer, 4-vinylphenol, chloroplatinic acid and DMF, and react at a speed of 200 r / min and a temperature of 70°C for 2 hours to obtain a functional monomer; evenly mix the functional monomer, 2,6-dimethylphenol, cupric chloride, pyridine and DMF, and react at a speed of 120 r / min, a temperature of 25°C and an oxygen atmosphere for 2 hours to obtain a functionalized polyphenylene ether.

[0022] The amount ratio of sodium hydroxide, isopropanol, methanol and 1,3-divinyltetramethyldisiloxane in step B1 is 200mmol:35mL:35mL:100mmol, the molar ratio of the intermediate to pentaerythritol tetrathioglycolate is 4:1, and the amount of benzophenone is 1% of the mass of the intermediate.

[0023] The amount of concentrated sulfuric acid used in step B2 is 1.5% of the mass of octamethylcyclotetrasiloxane, and the molar ratio of the starting monomer, the chain extension monomer and dimethylchlorosilane is 1:4:4.2.

[0024] The molar ratio of the modified monomer and 4-vinylphenol described in step B3 is 1:4, and the amount ratio of the functional monomer, 2,6-dimethylphenol, copper chloride, pyridine and DMF is 1g:20g:0.6g:50mL:200mL.

[0025] Example 2: A method for preparing an antistatic MPPE composite material based on CNT, comprising the following steps: Step A1: functionalized polyphenylene ether, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether were mixed, and the mixture was reacted at a speed of 200 r / min and a temperature of 0°C for 1.5 h to obtain modified polyphenylene ether; styrene, 4,4'-azobis(4-cyanopentanol) and toluene were uniformly mixed, nitrogen was introduced for protection, and the mixture was reacted at a speed of 120 r / min and a temperature of 70°C for 12 h to obtain hydroxylated polystyrene; Step A2: hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF were mixed, and reacted for 3 hours at a speed of 200 r / min and a temperature of 0°C to obtain modified polystyrene; carbon nanotubes were dispersed in ethanol, and KH550 and deionized water were added under stirring at a speed of 200 r / min and a temperature of 65°C, and reacted for 2 hours to obtain amino carbon nanotubes; Step A3: Evenly mix the amino carbon nanotubes, maleic anhydride, triethylamine and toluene, and reflux for reaction at a speed of 80 r / min and a temperature of 115°C for 3 hours to obtain modified carbon nanotubes. Weigh the following raw materials in parts by weight: 40 parts of modified polyphenylene ether, 50 parts of modified polystyrene, 13 parts of modified carbon nanotubes and 1.3 parts of zinc oxide. Extrude and granulate the raw materials at a temperature of 235°C to obtain an antistatic MPPE composite material based on CNT.

[0026] The amount ratio of the functionalized polyphenylene ether, furanyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether described in step A1 is 1 g:2 g:0.7 g:1 mL:50 mL, and the mass ratio of styrene, 4,4'-azobis(4-cyanopentanol) and toluene is 20:1.2:20.

[0027] The amount ratio of hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step A2 is 1 g:1.8 g:0.7 g:1 mL:50 mL, and the amount of KH550 is 2% of the mass of the carbon nanotubes.

[0028] The amount ratio of the amino carbon nanotubes, maleic anhydride, triethylamine and toluene described in step A3 is 1 g:50 mmol:150 mmol:30 mL.

[0029] The functionalized polyphenylene ether is prepared by the following steps: Step B1: Sodium hydroxide, isopropanol and methanol are mixed evenly, and stirred for 4 hours at a speed of 150 r / min and a temperature of 55° C., and then 1,3-divinyltetramethyldisiloxane and toluene are added, and the reaction is continued for 35 minutes to obtain an intermediate, and the intermediate, pentaerythritol tetrathioglycolate, benzophenone and DMF are mixed evenly, and the reaction is carried out for 1.5 hours at a speed of 60 r / min and irradiation with 365 nm ultraviolet light to obtain a starting monomer; Step B2: octamethylcyclotetrasiloxane and concentrated sulfuric acid are mixed evenly, and reacted at a speed of 120 r / min and a temperature of 80° C. for 4 hours to obtain a chain extension monomer, and the starting monomer, the chain extension monomer and DMF are mixed, and reacted at a speed of 150 r / min and a temperature of 65° C. for 10 hours, and then cooled to 15° C., dimethylchlorosilane is added, and the reaction is continued for 10 hours to obtain a modified monomer; Step B3: Evenly mix the modified monomer, 4-vinylphenol, chloroplatinic acid and DMF, and react at a speed of 200 r / min and a temperature of 75°C for 3 hours to obtain a functional monomer; evenly mix the functional monomer, 2,6-dimethylphenol, cupric chloride, pyridine and DMF, and react at a speed of 120 r / min, a temperature of 30°C and an oxygen atmosphere for 2 hours to obtain a functionalized polyphenylene ether.

[0030] The amount ratio of sodium hydroxide, isopropanol, methanol and 1,3-divinyltetramethyldisiloxane in step B1 is 200mmol:35mL:35mL:100mmol, the molar ratio of the intermediate to pentaerythritol tetrathioglycolate is 4:1, and the amount of benzophenone is 1% of the mass of the intermediate.

[0031] The amount of concentrated sulfuric acid used in step B2 is 1.5% of the mass of octamethylcyclotetrasiloxane, and the molar ratio of the starting monomer, the chain extension monomer and dimethylchlorosilane is 1:4:4.2.

[0032] The molar ratio of the modified monomer and 4-vinylphenol described in step B3 is 1:4, and the amount ratio of the functional monomer, 2,6-dimethylphenol, copper chloride, pyridine and DMF is 1g:20g:0.6g:50mL:200mL.

[0033] Embodiment 3: A method for preparing an antistatic MPPE composite material based on CNT, comprising the following steps: Step A1: functionalized polyphenylene ether, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether were mixed, and the mixture was reacted at a speed of 300 r / min and a temperature of 0°C for 1.5 h to obtain modified polyphenylene ether; styrene, 4,4'-azobis(4-cyanopentanol) and toluene were uniformly mixed, nitrogen was introduced for protection, and the mixture was reacted at a speed of 150 r / min and a temperature of 75°C for 12 h to obtain hydroxylated polystyrene; Step A2: hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF were mixed, and reacted for 3 hours at a speed of 300 r / min and a temperature of 0°C to obtain modified polystyrene; carbon nanotubes were dispersed in ethanol, and KH550 and deionized water were added under stirring at a speed of 300 r / min and a temperature of 70°C, and reacted for 3 hours to obtain amino carbon nanotubes; Step A3: Evenly mix the amino carbon nanotubes, maleic anhydride, triethylamine and toluene, and reflux for reaction at a speed of 80 r / min and a temperature of 120°C for 3 hours to obtain modified carbon nanotubes. Weigh the following raw materials in parts by weight: 50 parts of modified polyphenylene ether, 50 parts of modified polystyrene, 15 parts of modified carbon nanotubes and 1.5 parts of zinc oxide. Extrude and granulate the raw materials at a temperature of 240°C to obtain an antistatic MPPE composite material based on CNT.

[0034] The amount ratio of the functionalized polyphenylene ether, furanyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether described in step A1 is 1 g:2 g:0.7 g:1 mL:50 mL, and the mass ratio of styrene, 4,4'-azobis(4-cyanopentanol) and toluene is 20:1.2:20.

[0035] The amount ratio of hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step A2 is 1 g:1.8 g:0.7 g:1 mL:50 mL, and the amount of KH550 is 2% of the mass of the carbon nanotubes.

[0036] The amount ratio of the amino carbon nanotubes, maleic anhydride, triethylamine and toluene described in step A3 is 1 g:50 mmol:150 mmol:30 mL.

[0037] The functionalized polyphenylene ether is prepared by the following steps: Step B1: Sodium hydroxide, isopropanol and methanol are mixed evenly, and stirred for 5 hours at a speed of 150 r / min and a temperature of 60° C., and then 1,3-divinyltetramethyldisiloxane and toluene are added, and the reaction is continued for 40 minutes to obtain an intermediate, and the intermediate, pentaerythritol tetrathioglycolate, benzophenone and DMF are mixed evenly, and the reaction is carried out for 1.5 hours at a speed of 80 r / min and irradiation with 365 nm ultraviolet light to obtain a starting monomer; Step B2: octamethylcyclotetrasiloxane and concentrated sulfuric acid are mixed uniformly, and reacted at a speed of 150 r / min and a temperature of 80° C. for 5 hours to obtain a chain extension monomer; the starting monomer, the chain extension monomer and DMF are mixed, and reacted at a speed of 200 r / min and a temperature of 65° C. for 15 hours, then cooled to 15° C., dimethylchlorosilane is added, and the reaction is continued for 15 hours to obtain a modified monomer; Step B3: Evenly mix the modified monomer, 4-vinylphenol, chloroplatinic acid and DMF, and react at a speed of 300 r / min and a temperature of 80°C for 3 hours to obtain a functional monomer; evenly mix the functional monomer, 2,6-dimethylphenol, cupric chloride, pyridine and DMF, and react at a speed of 150 r / min, a temperature of 30°C and an oxygen atmosphere for 3 hours to obtain a functionalized polyphenylene ether.

[0038] The amount ratio of sodium hydroxide, isopropanol, methanol and 1,3-divinyltetramethyldisiloxane in step B1 is 200mmol:35mL:35mL:100mmol, the molar ratio of the intermediate to pentaerythritol tetrathioglycolate is 4:1, and the amount of benzophenone is 1% of the mass of the intermediate.

[0039] The amount of concentrated sulfuric acid used in step B2 is 1.5% of the mass of octamethylcyclotetrasiloxane, and the molar ratio of the starting monomer, the chain extension monomer and dimethylchlorosilane is 1:4:4.2.

[0040] The molar ratio of the modified monomer and 4-vinylphenol described in step B3 is 1:4, and the amount ratio of the functional monomer, 2,6-dimethylphenol, copper chloride, pyridine and DMF is 1g:20g:0.6g:50mL:200mL.

[0041] Comparative Example 1: Compared with Example 1, this comparative example uses carbon nanotubes instead of modified carbon nanotubes, and the other steps are the same.

[0042] Comparative Example 2: Compared with Example 1, this comparative example uses functionalized polyphenylene ether instead of modified polyphenylene ether, and the remaining steps are the same.

[0043] Comparative Example 3: Compared with Example 1, this comparative example uses ethanedithiol instead of pentaerythritol tetrathioglycolate, and the other steps are the same.

[0044] Comparative Example 4: Compared with Example 1, bisphenol A is used to replace the functional monomer in this comparative example, and the remaining steps are the same.

[0045] The composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were made into Type 1A specimens according to the standard of GB / T1040.1-2018 to test the tensile strength, and were made into Type A specimens according to the standard of GB / T1843-2008 to test the impact strength. The test results are shown in Table 1 below.

[0046] Table 1

[0047] It can be seen from Table 1 that the present invention has good mechanical properties.

[0048] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing an antistatic MPPE composite material based on CNT, characterized in that: The specific steps include: Step A1: functionalized polyphenylene ether, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether are mixed and reacted to obtain modified polyphenylene ether, styrene, 4,4'-azobis(4-cyanopentanol) and toluene are uniformly mixed, nitrogen is introduced for protection, and the mixture is reacted to obtain hydroxylated polystyrene; Step A2: hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF are mixed and reacted to obtain modified polystyrene, carbon nanotubes are dispersed in ethanol, stirred and KH550 and deionized water are added to react to obtain amino carbon nanotubes; Step A3: The amino carbon nanotubes, maleic anhydride, triethylamine and toluene are mixed and refluxed to react to obtain modified carbon nanotubes, and the following raw materials are weighed in parts by weight: 40-50 parts of modified polyphenylene ether, 40-50 parts of modified polystyrene, 10-15 parts of modified carbon nanotubes and 1-1.5 parts of zinc oxide. The raw materials are extruded and granulated to obtain an antistatic MPPE composite material based on CNT.

2. The method for preparing an antistatic MPPE composite material based on CNT according to claim 1, characterized in that: The amount ratio of the functionalized polyphenylene ether, furanyl chloride, 4-dimethylaminopyridine, triethylamine and ethylene glycol dimethyl ether described in step A1 is 1 g:2 g:0.7 g:1 mL:50 mL, and the mass ratio of styrene, 4,4'-azobis(4-cyanopentanol) and toluene is 20:1.2:

20.

3. The method for preparing an antistatic MPPE composite material based on CNT according to claim 1, characterized in that: The amount ratio of hydroxylated polystyrene, furanoyl chloride, 4-dimethylaminopyridine, triethylamine and DMF described in step A2 is 1 g:1.8 g:0.7 g:1 mL:50 mL, and the amount of KH550 is 2% of the mass of the carbon nanotubes.

4. The method for preparing an antistatic MPPE composite material based on CNT according to claim 1, characterized in that: The amount ratio of the amino carbon nanotubes, maleic anhydride, triethylamine and toluene described in step A3 is 1 g:50 mmol:150 mmol:30 mL.

5. The method for preparing an antistatic MPPE composite material based on CNT according to claim 1, characterized in that: The functionalized polyphenylene ether is prepared by the following steps: Step B1: After mixing and stirring sodium hydroxide, isopropanol and methanol, 1,3-divinyltetramethyldisiloxane and toluene are added to react to obtain an intermediate, and the intermediate, pentaerythritol tetrathioglycolate, benzophenone and DMF are mixed to react to obtain a starting monomer; Step B2: octamethylcyclotetrasiloxane and concentrated sulfuric acid are mixed and reacted to obtain a chain extension monomer, and the starting monomer, the chain extension monomer and DMF are mixed and reacted, and then the temperature is reduced and dimethylchlorosilane is added to continue the reaction to obtain a modified monomer; Step B3: The modified monomer, 4-vinylphenol, chloroplatinic acid and DMF are mixed and reacted to obtain a functional monomer, and the functional monomer, 2,6-dimethylphenol, cupric chloride, pyridine and DMF are mixed and reacted to obtain a functionalized polyphenylene ether.

6. The method for preparing an antistatic MPPE composite material based on CNT according to claim 5, characterized in that: The amount ratio of sodium hydroxide, isopropanol, methanol and 1,3-divinyltetramethyldisiloxane in step B1 is 200mmol:35mL:35mL:100mmol, and the molar ratio of the intermediate to pentaerythritol tetrathioglycolate is 4:

1.

7. The method for preparing an antistatic MPPE composite material based on CNT according to claim 5, characterized in that: The amount of concentrated sulfuric acid used in step B2 is 1.5% of the mass of octamethylcyclotetrasiloxane, and the molar ratio of the starting monomer, the chain extension monomer and dimethylchlorosilane is 1:4:4.

2.

8. The method for preparing an antistatic MPPE composite material based on CNT according to claim 5, characterized in that: The molar ratio of the modified monomer and 4-vinylphenol described in step B3 is 1:4, and the amount ratio of the functional monomer, 2,6-dimethylphenol, copper chloride, pyridine and DMF is 1g:20g:0.6g:50mL:200mL.

9. An antistatic MPPE composite material based on CNT, characterized in that: Prepared according to any one of the preparation methods described in claims 1-8.

Citation Information

Patent Citations

  • Furyl-containing styrene copolymers and preparation method thereof

    CN107245134A

  • Polypropylene composite material and preparation method thereof

    CN118388885A

  • Nanofiber loaded with nanofiller as well as preparation method and application of nanofiber

    CN118668327A

  • Antistatic polyphenyl ether resin composition as well as preparation method and application thereof

    CN118725537A

  • Graphene-based antistatic PC composite material and preparation method thereof

    CN119432093A

Cited By

  • High-wear-resistance Krah pipe and preparation method thereof

    CN120173343A

  • Anti-static Mppo material based on carbon nanotubes and preparation method of anti-static Mppo material

    CN121203374A

  • Antistatic composite material based on carbon nanotubes and preparation method thereof

    CN122404868A